Comparison of three techniques for detection of Chlamydia trachomatis in endocervical specimens from asymptomatic women. - Lefebvre, J (1988)
Culture in DEAE-dextran-treated HeLa 229 cells, a solid-phase enzyme immunoassay (EIA) (Chlamydiazyme; Abbott Laboratories, North Chicago, Ill.), and a direct immunofluorescence test (DFA) (MicroTrak; Syva Co., Palo Alto, Calif.) were compared for the detection of Chlamydia trachomatis in endocervical specimens from 715 asymptomatic women. Response to antibiotic therapy was also monitored at least 4 weeks after completion of therapy. An additional sample was collected at a control visit, and a second culture was performed if discrepancies were observed between the three tests. A total of 48 infections were diagnosed, for a prevalence of 6.7%. At the first visit, 37 specimens were positive by culture. The respective sensitivities of EIA and DFA were 78.4 and 81.1% and the respective specificities were 96.8 and 97.9% when compared with the cell culture technique. The positive predictive values were 56.9 and 68.2%, respectively. When the additional 11 infections detected by the second culture were included to establish a new standard of positivity, the sensitivity of the first culture was estimated at 77.1%. The positive predictive values of EIA and DFA increased to 77.6 and 83.7%, respectively. EIA and DFA performed as well as culture for control of therapy; a 100% agreement among the three techniques was observed.